2021
DOI: 10.19206/ce-143486
|View full text |Cite
|
Sign up to set email alerts
|

Model tests of a marine diesel engine powered by a fuel-alcohol mixture

Abstract: The paper presents the results of model and empirical tests conducted for a marine diesel engine fueled by a blend of n-butanol and diesel oil. The research were aimed at assessing the usefulness of the proprietary diesel engine model in conducting research on marine engines powered by alternative fuels to fossil fuels. The authors defined the measures of adequacy. On their basis, they assessed the adequacy of the mathematical model used. The analysis of the results of the conducted research showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Publication [26] presents the results of empirical research and tests of the developed mathematical model of a marine engine powered by a mixture of diesel oil and n-butanol. Benefits in terms of pollutant emissions were found when using biological additives to power the engine.…”
Section: Introductionmentioning
confidence: 99%
“…Publication [26] presents the results of empirical research and tests of the developed mathematical model of a marine engine powered by a mixture of diesel oil and n-butanol. Benefits in terms of pollutant emissions were found when using biological additives to power the engine.…”
Section: Introductionmentioning
confidence: 99%
“…Many publications refer to the use of alcohol fuels in internal combustion engines and their impact on the operating parameters of such engines such as vibration and the way they are measured [6,27], noise intensity [13], energy efficiency [2] or reduction in the number of harmful exhaust components [15,23]. Ongoing research has shown that the use of alcohol addi-tives and alcohol as a stand-alone fuel both in sparkignition engines [16,25] and diesel engines [17,30] can significantly affect the engine performance. In the case of spark-ignition engines, ethyl and methyl alcohol fuels are among the most widely studied alternative fuels due to their relatively low viscosity and high vapor pressure.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is the extremely wide application of ICE has caused a number of global problems, related to the depletion of world oil reserves, atmospheric pollution with toxic substances, global warming etc. There is a solution that allows to partially solve the mentioned problems through application of alternative fuels in internal combustion engines [3,7,10,13,15]. In this content a water-fuel emulsion (WFE) could be treated as one of the most promising type of alternative fuels due to the combination of the unique properties, characteristics, production and operation features [1,2,5,14].…”
Section: Introductionmentioning
confidence: 99%